Context, design and conduct of the longitudinal COVID‐19 psychological research consortium study–wave 3. Issue 3 (22nd May 2021) - McBride, Orla; Butter, Sarah; Murphy, Jamie; Shevlin, Mark; Hartman, Todd K.; Hyland, Philip; McKay, Ryan; Bennett, Kate M.; Gibson‐Miller, Jilly; Levita, Liat; Mason, Liam; Martinez, Anton P.; et al.
Abstract: Objectives: The COVID‐19 Psychological Research Consortium (C19PRC) Study aims to assess the impact of the COVID‐19 pandemic in the adult population in multiple countries. This paper describes the third wave of the UK survey (the 'parent' strand of the Consortium) during July‐August 2020. Methods: Adults ( N = 2025) who participated in the baseline and/or first follow‐up surveys were reinvited to participate in this survey, which assessed: (1) COVID‐19 related knowledge, attitudes, and behaviours; (2) the occurrence of common mental disorders; as well as the role of (3) psychological factors and (4) social and political attitudes, in influencing the public's response to the pandemic. Weights were calculated using a survey raking algorithm to ensure that the cross‐sectional sample is nationally representative in terms of gender, age, and household income, and representative of the baseline sample characteristics for household composition, ethnicity, urbanicity and born/raised in UK. Results: 1166 adults (57.6% of baseline participants) provided full interviews at Wave 3. The raking procedure successfully re‐balanced the cross‐sectional sample to within 1% of population estimates across selected socio‐demographic characteristics. Conclusion: This paper demonstrates the strength of the C19PRC Study data to facilitate and stimulate interdisciplinary research addressing important public health questions relating to the COVID‐19 pandemic.